2020
DOI: 10.1002/qj.3803
|View full text |Cite
|
Sign up to set email alerts
|

The ERA5 global reanalysis

Abstract: Within the Copernicus Climate Change Service (C3S), ECMWF is producing the ERA5 reanalysis which, once completed, will embody a detailed record of the global atmosphere, land surface and ocean waves from 1950 onwards. This new reanalysis replaces the ERA-Interim reanalysis (spanning 1979 onwards) which was started in 2006. ERA5 is based on the Integrated Forecasting System (IFS) Cy41r2 which was operational in 2016. ERA5 thus benefits from a decade of developments in model physics, core dynamics and data assim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

102
9,758
6
48

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15,558 publications
(9,914 citation statements)
references
References 137 publications
102
9,758
6
48
Order By: Relevance
“…New ways of estimating the forcing term in the SST evolution equation should also be exploited. In the present study, the forcing was approximated by a low pass filtered SST temporal derivative but, in principle, heat fluxes estimates given by model-derived reanalyses, e.g., the ECMWF ERA-5, or estimated using bulk formulae could be tested [45,46]. In addition, the possibility to refine the temporal resolution of the method input parameters (e.g., σ u,v and h), presently given by climatological two-dimensional maps, could further improve the reconstruction method capabilities.…”
mentioning
confidence: 99%
“…New ways of estimating the forcing term in the SST evolution equation should also be exploited. In the present study, the forcing was approximated by a low pass filtered SST temporal derivative but, in principle, heat fluxes estimates given by model-derived reanalyses, e.g., the ECMWF ERA-5, or estimated using bulk formulae could be tested [45,46]. In addition, the possibility to refine the temporal resolution of the method input parameters (e.g., σ u,v and h), presently given by climatological two-dimensional maps, could further improve the reconstruction method capabilities.…”
mentioning
confidence: 99%
“…The representation of the troposphere and tropical cyclones is better, as is the soil moisture, the balance of precipitation and evaporation, and the consistency between sea surface temperature and sea ice. The data assimilation system is also renewed (IFSCycle 41r2 4D-Var), and a vast amount of historical observations (satellite or in situ) are assimilated [24].…”
Section: Era5 Reanalysismentioning
confidence: 99%
“…It presents a 30-km global grid and uses 137 vertical levels from the surface up to a height of 80 km. The entire dataset from 1950-present will be available soon, substantially extending the period of ERA-Interim (1979-present), with a much higher spatial and temporal resolution [24]. Furthermore, recent studies in real wind farms have shown that ERA5 can be the new "champion" of wind energy modeling [25].…”
Section: Era5 Reanalysismentioning
confidence: 99%
See 1 more Smart Citation
“…This run tests the performance of the high-resolution two-way coupled ocean-atmosphere model. The atmosphere is initialized using the ECMWF ERA5 reanalysis dataset, with a grid resolution of 30 km (Hersbach, 2016). The same data also provide the boundary conditions for air temperature, wind speed, and air humidity every six hours.…”
Section: Experiments Design and Observational Datasetsmentioning
confidence: 99%